NOTCH receptors in gastric and other gastrointestinal cancers: oncogenes or tumor suppressors?. Issue 1 (December 2016) - Huang, Tingting; Zhou, Yuhang; Cheng, Alfred; Yu, Jun; To, Ka; Kang, Wei
Abstract Gastric cancer (GC) ranks the most common cancer types and is one of the leading causes of cancer-related death. Due to delayed diagnosis and high metastatic frequency, 5-year survival rate of GC is rather low. It is a complex disease resulting from the interaction between environmental factors and host genetic alterations that deregulate multiple signaling pathways. The Notch signaling pathway, a highly conserved system in the regulation of the fate in several cell types, plays a pivotal role in cell differentiation, survival and proliferation. Notch is also one of the most commonly activated signaling pathways in tumors and its aberrant activation plays a key role in cancer advancement. Whether Notch cascade exerts oncogenic or tumor suppressive function in different cancer types depends on the cellular context. Mammals have four NOTCH receptors that modulate Notch pathway activity. In this review, we provide a comprehensive summary on the functional role of NOTCH receptors in gastric and other gastrointestinal cancers. Increasing knowledge of NOTCH receptors in gastrointestinal cancers will help us recognize the underlying mechanisms of Notch signaling and develop novel therapeutic strategies for GC.